Instant Andean beverage based on toasted grains: design and optimization (Bioagro, 2022)
Grains in high Andean areas have various nutritional compounds, but due to their sensory qualities, they are only consumed fresh or dehydrated. A processing alternative is the roasting of the beans to obtain beverages. The objective of the study was to evaluate the temperature and roasting time on the solubility and the color difference (ΔE) of the pea, barley and broad beans, in order to determine the optimal roasting parameters, as well as design the optimal mixture of grains to obtain an instant beverage. In a first stage, a rotational central composite design was used to optimize the roasting process based on solubility and ΔE. In a second stage, a simplex-centroid design was applied to determine the optimal mixture of roasted flour for the instant beverage. The roasted barley grains had the highest solubility, and the highest ΔE was for roasted pea beans. The roasting temperature had a significant effect (P≤0,05) on the solubility of the barley and pea grains, while the time and the roasting temperature exhibited a significant effect on the ΔE of the three grain types. The optimal roasting parameters were different for each bean. Beverages with high percentages of bean and barley flour, and low percentages of pea flour had greater acceptability. It is concluded that instant beverages with high acceptability can be obtained from grains grown in Andean zones.
Keywords: aceptability; beverage; Hordeum vulgare; Pisum sativum; Vicia faba